Studies of the Separation of Nitrate Complexes of Samarium(III) from Neodymium(III) in the CHOH-7 M HNO System on the Strongly Basic Anion Exchanger Wofatit SBW - Z. Hubicki; M. Olszak (Adsorption Science & Technology)
The application of frontal analysis for the purification of Sm III from Nd III in aqueous nitric acid/alcohol medium was studied. This problem was investigated by purifying quantities of samarium(III) from 1% neodymium(III) in the Ln(NO 3 ) 3 –90% v/v C 2 H 5 OH-10% v/v 1 or 7 M HNO 3 system (concentration ca. 5.231 g Ln 2 O 3 /dm 3 ) on strongly basic anion exchangers with different degrees of crosslinkage. The anion exchangers studied can be categorized in terms of their order of applicability: thus, in the system 90% v/v C 2 H 5 OH-10% v/v 1 M HNO 3 , Lewatit MP 5080 > Wofatit SBW × 8% DVB > Wofatit SBW × 6% DVB > Wofatit SBW × 12% DVB ≥ Wofatit SBW × 4% DVB ≥ Wofatit SBW × 7% DVB > Wofatit SBW × 2% DVB > Wofatit SBW × 16% DVB, whilst in the system 90% v/v C 2 H 5 OH-10% v/v 1 M HNO 3 , Lewatit MP 5080 > Wofatit SBK × 7% DVB ≥ Wofatit SBW × 6% DVB ≥ Wofatit SBW × 4% DVB > Wofatit SBW × 8% DVB ≥ Wofatit SBW × 2% DVB ≥ Wofatit SBW × 12% DVB = Wofatit SBW × 16% DVB. The most effective results were obtained with the anion exchanger Lewatit MP 5080. Using a 1 dm 3 bed of this anion exchanger, it was possible to purify 0.2 kg Sm 2 O 3 and achieve a decrease in its neodymium content from 1% to < 0.001%.